Cystatin (C) and its correlation to ischemic heart disease - Saeed, Basil N. (AL-Kindy College Medical Journal, 2015)
Background: Cystatin C is recently considered to be a good predictor of cardiovascular morbidity and mortality in patients with coronary artery disease (CAD)Objectives: Correlation between cystatin and ischemic heart disease.Methods :One hundred forty patients (140) with ischemic heart disease admitted to thin study at Baghdad teaching hospital from the period June. 2011 to Jan. 2012. Those patients was categorized into three groups.Group (A): patients with ischemic heart failure.Group (B): Patients with myocardial infarction.Group (C) patients with unstable angina.All these groups were in comparison to fifty (50) healthy controls. Fasting serum citation (C) were measured in all patients and control in addition to all other routine investigations.Results: All results of serum cystatin C in all three groups of patients were higher in comparison to control group (P. value < 0.05) while it was not significantly different between the three groups (P. value 0.05)Conclusion: Cytstatin C can be used as prognostic biomarker in patients with ischemic heart and its complicated.